Activable Multi-Modal Nanoprobes for Imaging Diagnosis and Therapy of Tumors - Yang, Yan; Yue, Saisai; Qiao, Yuanyuan; Zhang, Peisen; Jiang, Ni; Ning, Zhenbo; Liu, Chunyan; Hou, Yi (Frontiers in Chemistry, 2021)
Malignant tumor has become one of the major diseases that cause human death, but there remains a lack of effective methods for tiny tumor diagnosis, metastasis warning, clinical efficacy prediction, and effective treatment. In this context, localizing tiny tumors via imaging and non-invasively extracting molecular information related to tumor proliferation, invasion, metastasis, and drug resistance from the tumor microenvironment have become the most fundamental issues faced by cancer studies. Tumor associated microenvironmental physiological parameters, such as hypoxia, acidic extracellular pH, protease, reducing conditions, and so forth, have much to do with prognostic indicators for cancer progression, and impact the therapeutic administrations. By combining with various novel nanoparticle-based activatable probes, the molecular imaging technologies provide a feasible approach to visualize tumor-associated microenvironment parameters noninvasively, and realize accurate treatment of tumor. This review focuses on the recent achievements in the designs of “smart” nanomedicine responding to the tumor microenvironment-related features, and highlights the state of the art in tumor imaging diagnosis and therapy.